Chromobacterium violaceum Isolated from a Wound Sepsis: A Case Study from Nepal - Shamshul Ansari; Pramod Paudel; Kishor Gautam; Sony Shrestha; Sangita Thapa; Rajendra Gautam (Case Reports in Infectious Diseases)
Chromobacterium violaceum is a facultative anaerobic, Gram-negative rod, prevalent in tropical and subtropical regions. It enters through the skin injury and is capable of causing severe systemic infections leading to septic shock and multiorgan failure. It has been reported by few authors across the world but this is probably the first case of Chromobacterium violaceum isolated from wound sepsis from Nepal. In this study, a pus sample from the infection of a prick injury in the left middle finger was collected from the patient admitted to the intensive care unit. Bacteriological investigations of the pus sample revealed the causative organism to be Chromobacterium violaceum. This case study indicates that Chromobacterium violaceum can act as a potential cause of wound sepsis that may lead to the septic shock and if not treated timely, the mortality rate can be high as was in this study. Although this organism is very rare, the infection caused requires prompt treatment to minimize the mortality rate. Therefore, we recommend the timely diagnosis and antimicrobial therapy of this infection to combat the consequences led.